Pengaruh Dana Pihak Ketiga (DPK), Angkatan Kerja, dan Investasi (PMDN dan PMA) Terhadap Pertumbuhan Ekonomi Di Kalimantan Barat - B01110019, HENDRI SETIAWAN (Jurnal Pembangunan dan Pemerataan, 2016)
The research aimed at knowing and analizing the effect of the third party funds,workforce, and PMDN and PMA investment on economic development of West Kalimantan.The study employed descriptive quantitative research using secondary data that was timeseries which were gathered from Central Bureau of Statistics and Bank Indonesia of WestKalimantan. The data was analyzed by Eviews-6 Observation for 30 year data between 1984 and2013 in West Kalimantan province.The research finding showed that simultaneously the Third Funds, Workforce, andPMDN and PMA investment gave significant effect on the economic development, whilepartially the Third Funds had positive impact but not significant on the economic development.Furthermore, Workforce and PMA investment had positive and significant influence oneconomic development of West Kalimantan.Keywords: The Third Party Funds, Workforce, and PMDN and PMA Investment andEconomic Development.